To solve the equation \(-4(2x+1)+4x+3=-17\), we'll start by distributing the \(-4\) on the left-hand side:
\[ -4(2x) - 4(1) + 4x + 3 = -17 \]
This simplifies to:
\[ -8x - 4 + 4x + 3 = -17 \]
Next, combine like terms:
\[ (-8x + 4x) + (-4 + 3) = -17 \]
This simplifies to:
\[ -4x - 1 = -17 \]
Now, add \(1\) to both sides of the equation:
\[ -4x - 1 + 1 = -17 + 1 \]
Which simplifies to:
\[ -4x = -16 \]
Now, divide both sides by \(-4\):
\[ x = 4 \]
Thus, the solution to the equation is:
\[ \boxed{4} \]